MAP BASIS AND USING OF COMPUTERS AND GIS FOR TRANSPORT LINE DESIGN (Perner's Contacts, 2010)
This paper deals with possibilities of public transport line design. There are mentioned advantages and disadvantages of several methods including the evaluation of difficulty of their use.
Keywords: transport; transport line design; GIS; chart; snapshot